Thermal and combustion behaviors of aluminum/manganese dioxide/fluoroelastomer terpolymer nanothermite - Song, Jiaxing (2023)
Fluoroelastomer has received increasing attention for energetic materials application due to its high fluorine contents. Different contents (0 wt%–30 wt%) of poly(VDF-ter-HFP-ter-TFE) terpolymer are added into Al/MnO2 nanothermite. The peak exothermic temperature of thermite reaction for Al/MnO2 system is about 554°C with 1070 Jg−1 heat release. After adding terpolymer, it mainly exists in the gap among Al nanoparticles and MnO2 nanorods, and react with Al and MnO2 at the range of 350 to 540°C before the occurrence of the thermite reaction. 10 wt% terpolymer has relatively little effect on the thermite reaction, but for the samples with higher terpolymer content, more nanothermite components react with terpolymer at an early stage. Ignition and combustion performance show terpolymer can reduce ignition current threshold by up to 9.82% and increase combustion duration time at least several times. The potential reasons for the above results are analyzed. This work can shed light on the application of fluoroelastomer in energetic-materials.